أسباب الإلحاد المعاصر: دراسة في فهم طلاب جامعات عمان، الأردن: Causes of the New Atheism: A Study on its Understanding Among Universities Students in Amman, Jordan - Friawan, Main Sayel; Abd. Latif, Faizuri; Saged, Ali Ali Gobaili (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Atheism is a belief that rejects the existence of God and supernatural. The paper examines the understanding of Arab teenagers, especially students at the University of Amman, Jordan on the phenomenon of atheism in the Arab world. This field-based study selected 7584 students as a sample where identification focused on their understanding of the characteristics and factors of adolescent involvement with atheism. Studies have found that the characteristic of atheism is to deny the existence of Allah SWT and the role of prophet, rejecting religious authority and admire the progress from the West. While the biggest finding of the factors involved with atheism is because they have an extreme attitude and an empty soul due to the scarcity of religious knowledge.